Research procedure acceptability through women during pregnancy and postpartum: A pilot study - Simon, Julien; Thisse, Jeanne; Chabert, Camille; Barasinski, Chloé; Ambroise Grandjean, Gaëlle (International journal of gynecology and obstetrics, 2024)
Objective To assess the feasibility and relevancy of a systematic data collection process in characterizing factors influencing research acceptability through women during pregnancy and early postpartum. Methods A pilot prospective observational crossover unicentric study was conducted in Est France. All the women (except language barrier and intensive care transfer) were called upon to complete a survey (33 questions). The primary endpoints were the participation rate and the completeness of the information. The secondary endpoint was the participants' sociodemographic background and preferences regarding research (bivariate analysis, P value <0.20). Results Within the research period (February 23–March 8, 114 childbirths), 105 women fitting the criteria were called upon for the survey. The participation rate and completeness were high. The participation rate was 93% with six lost to follow‐up, and one refusal. The global filling rate was 95%. We highlighted two plausible variables of interests for research participation: women age older (P value 0.119) and level of education (P value 0.176). A sufficient cooling‐off period, the commitment of women's health providers, and the possibility to accede research results might favor women's involvement. Acceptability would appear to be decreasing when the protocol implied fetal or neonatal data collection (compared to maternal data), unless research led to a better therapeutic option. Conclusion The data collection process is highly feasible and provide consistent data. Larger‐scale output obtention should enhance the conception and rollout of projects, first by calculating sample size based on potentials for recruitments adjusted to populations, characteristics and second by fitting the experimental design to women's expectations. Synopsis The pilot study aims to contextualize perinatal research results, facilitate research implementation and promote evidence‐based medicine and midwifery.